Regulation of MITF and TFEB - Friedrichsen, H (2016)
The bHLH-LZ transcription factors MITF and TFEB have been implicated in human disease, with their overexpression increasing the risk of developing cancer. The manner in which their access to E-box target motifs is controlled is an important consideration, as it is via binding to these motifs that bHLH-LZ factors mediate changes in gene expression. In addition to controlling the level of a given transcription factor, mounting evidence suggests that modulating MITF target specificity and TFEB access to the nucleus constitute an important means of regulating their functional output. Post-translational modifications offer one mechanism by which stimuli can rapidly and reversibly alter MITF and TFEB binding to their transcriptional targets. This thesis aims to expand upon the already substantial literature examining MITF and TFEB post-translational modifications. Specifically, we confirm that MITF can be acetylated and that this occurs within the basic region of the DNA binding domain. Using a naturally occurring acetylation-mimicking mutation, we study the possible functional implications of acetylation on MITF residue K206. Turning to the closely related TFE family member TFEB, we show that TFEB nuclear translocation in response to multiple stimuli is reversible and at least partially mediated by a novel nuclear export signal in the TFEB N-terminus. We show that phosphorylation of nearby S138 by GSK3 requires a priming phosphorylation on S142 and that this latter event may activate an adjacent nuclear export signal.